Altered functional connectivity of the dorsal attention network among problematic social network users. (May 2021) - Lee, Deokjong; Lee, Junghan; Namkoong, Kee; Jung, Young-Chul
Highlights: FC of attention networks in problematic social network users was analyzed. FC of the DAN was strong for middle occipital gyrus and weak for DLPFC. Altered FC between the DAN and DLPFC was correlated with time spent on social media. Abstract: Many smartphone users spend excessive amounts of time online and cannot control their behavior, and the addictive overuse of social-networking services has been shown to be associated with diminished executive control. Attentional control is a cognitive process crucial to exerting executive functions. The purpose of this study was to investigate functional connectivity (FC) characteristics of attention networks in problematic social-network users. We performed seed-based resting-state FC analyses for 29 males and 10 females with excessive social network use and 32 healthy males and 17 healthy females. The right intraparietal sulcus and frontal eye fields were considered seeds of the dorsal attention network (DAN), and the right temporoparietal junction and ventral frontal cortex were considered seeds of the ventral attention network (VAN). Clinical characteristics predictive of FC findings in problematic social network users were identified through hierarchical multiple regression analysis. In FC analysis with DAN seeds, FC between the right intraparietal sulcus and the right middle occipital gyrus was stronger in problematic social network users than in controls, and FC between the right frontal eye field and the right dorsolateral prefrontal cortex was weaker than that in controls. There was no significant difference between the groups in FC analysis with VAN seeds. Hierarchical regression analyses showed that usage times on social networking platforms significantly predicted the negative effects on the strength of FC between the intraparietal sulcus and the dorsolateral prefrontal cortex. These findings indicated that problematic social network use reflects changes in the neural circuits underlying attentional control. Weaking of prefrontal control for attention networks would have a significant impact on failure to control one's time spent on social networks.